2022
DOI: 10.3389/fnins.2022.858404
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Hemispheric Asymmetry in Comatose Adults Receiving Extracorporeal Membrane Oxygenation

Abstract: Peripheral veno-arterial extracorporeal membrane oxygenation (ECMO) artificially oxygenates and circulates blood retrograde from the femoral artery, potentially exposing the brain to asymmetric perfusion. Though ECMO patients frequently experience brain injury, neurologic exams and imaging are difficult to obtain. Diffuse correlation spectroscopy (DCS) non-invasively measures relative cerebral blood flow (rBF) at the bedside using an optical probe on each side of the forehead. In this study we observed interhe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Various methods have been used to measure CA in ECMO patients. These methods include NIRS-derived rSO 2 [11,[33][34][35][46][47][48], oxyhemoglobin concentration [49], and total hemoglobin concentration [50], in addition to TCD-derived [51] and DCS-derived [42,52] CBF. Of note, each of these methods is used to derive a unique CA index, none of which is a gold standard.…”
Section: Monitoring Of Camentioning
confidence: 99%
See 2 more Smart Citations
“…Various methods have been used to measure CA in ECMO patients. These methods include NIRS-derived rSO 2 [11,[33][34][35][46][47][48], oxyhemoglobin concentration [49], and total hemoglobin concentration [50], in addition to TCD-derived [51] and DCS-derived [42,52] CBF. Of note, each of these methods is used to derive a unique CA index, none of which is a gold standard.…”
Section: Monitoring Of Camentioning
confidence: 99%
“…Early studies identified an association between the incidence of right-sided cerebral injury and carotid artery cannulation [81][82][83][84]. However, asymmetric cerebral perfusion has also been reported in a mixed population of adults on both VV and VA ECMO, none of whom underwent carotid artery cannulation [52]. The role of carotid artery cannulation in lateralized cerebral damage and neurological injury remains to be elucidated, as many other investigations have failed to identify this association [66,75,77,[85][86][87][88][89][90][91].…”
Section: Cannulation Sitementioning
confidence: 99%
See 1 more Smart Citation
“…This study showed similarities in the detection of high hemispheric asymmetry in comatose patients on ECMO between TCD and DCS. 92…”
Section: Continuous Neuromonitoring Devicesmentioning
confidence: 99%
“…This study showed similarities in the detection of high hemispheric asymmetry in comatose patients on ECMO between TCD and DCS. 92 Furthermore, DCS may be used to identify CA disruptions, potentially indicating impending brain injury. A prospective feasibility study used DCS and FD-DOS to measure CBF, hemoglobin concentrations, and optical scattering in nine neonates on ECMO.…”
Section: Noninvasive Optical Monitoring Modalitiesmentioning
confidence: 99%